Situational conditions and adolescent offending: Does the impact of unstructured socializing depend on its location?. (July 2014) - Hoeben, Evelien; Weerman, Frank
This study aims to identify the locations where unstructured socializing is related to adolescent offending. 'Locations' refer to private, semi-public and public spaces, which are further categorized into public entertainment, public transportation, other semi-public settings, streets, shopping centres and open spaces. Detailed longitudinal data, derived from space–time budget interviews among 615 respondents in the age range 11–20 years, about hourly activities and the whereabouts of adolescents are analysed. A random intercept panel model is used to control for selection effects that occur when crime-prone individuals prefer crime-conducive locations to other locations. Findings indicate that unstructured socializing is positively related to offending and that this relationship strongly depends on the location in which it occurs.